Metode Autoregressive Integrated Moving Average (Arima) dalam Memprediksi Produksi Tembakau Sumatera Utara - Meysin Andira (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Tobacco is one of the economic crops that has an important role in the global and national economy. In the production and selling price of tobacco is not only influenced by internal factors, such as cultivation methods and agricultural techniques and also external factors, In an effort to overcome this challenge One promising approach is the use of statistical methods and machine learning to combine data on these diverse factors. Autoregressive Integrated Moving Average (Arima) method. In 2010-2021, North Sumatra Province had 12 regencies that had the potential for tobacco production consisting of 12 years with 5 regencies in North Sumatra that had the potential to produce tobacco. Based on the forecast results, there was a significant increase in the amount of higher tobacco production in even years or it can be said to be an increase in the following 2 years. This can be a reference for producers to increase productivity in odd years to meet stable market needs.